A forest of symbols : art, science, and truth in the long nineteenth century - Pop, Andrei (Zone Books, 2019)
A groundbreaking reassessment of Symbolist artists and writers that investigates the concerns they shared with scientists of the period--the problem of subjectivity in particular.